Big Five Personality (OCEAN) : An Analysis in J.K. Rowling's Movie Harry Potter and the Philosopher's Stone - Syamsul Bahri; Ruth Manurung; Margareta Sitorus; Frianka Sitanggang; Jesika Sitorus (International Journal of Educational Development, 2024)
"Harry Potter and the Philosopher's Stone," a big movie released in 2001. The movie succeeded J.K. Rowling's fantasy novel of the same name. The film shows different characters and different characters. This study examines this description of personality through the lens of the Big Five personality model (OCEAN: Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism). By examining how the characters interact and behave, this study aims to identify the ways in which the characters display the characteristics associated with each of the Five Five personality traits. Using a descriptive method, the analysis focuses on the dialogue and monologues of the characters, supplemented by extensive library research on personality psychology, the Big Five Personality theory, and cinematic analysis. The study found that the characters in this movie possess characteristics related to the Big Five pattern, which can be seen in their actions, speech and behavior throughout the film. The results showed that openness to experience, extraversion, and neuroticism were the most prominent traits, while conscientiousness and flexibility were less common. It is important to understand how people affect people, because it determines how people act and how they treat others. Examining the characters in this movie not only enhances the viewing experience of the film, but also enhances the value of the Big Five model for analyzing characters in various literary and film works.